Nutritional and chemical composition of different life stages of Tribolium castaneum (Herbst). (September 2021) - Duarte, S.; Limão, J.; Barros, G.; Bandarra, N.M.; Roseiro, L.C.; Gonçalves, H.; Martins, L.L.; Mourato, M.P.; Carvalho, M.O.
Abstract: Tribolium castaneum can survive in extremely dry environments and be one of the major insect pests of broken and processed grains or other stored dried foods. Additionally, this species has demonstrated resistance to some classes of insecticides. The objective of this work was to evaluate the nutritional and chemical composition of T. castaneum, reared on maize flour, and compare protein, lipids and fatty acids profile, amino acids and mineral contents, of different developmental stages: larvae, pupae and adults. In general all stages were rich in protein (15.3% for larvae and 17.0% for adults, wet body weight). Disparities among developmental stages regarding amino acids and fatty acids content were found. Essential amino acids were most abundant in T. castaneum ; a different essential amino acid was prevalent on each developmental stage: larvae - valine; pupae - lysine; adults - histidine. Tribolium castaneum is rich in phosphorus, potassium and sulphur; larvae had a significantly higher content of phosphorus, potassium, sulphur and zinc, while adults showed significantly lower content of potassium and zinc. Larvae and pupae showed higher values of SFA (heptadecanoic and stearic acid) and PUFA (α-linolenic and linolenic acids), while MUFA showed the reverse tendency, with adults having the highest contents of hypogeic, palmitoleic and oleic acids. The nutritional differences among different developmental stages identified are due to specificities of each stage (level of chitinization, motility, energy requirements and food intake habits), as the diet offered to the insects was the same. This study can thus be considered a first step towards future directions of investigation, to a better understanding of this pest nutritional preferences and alternatives to achieve a more sustainable management of infested stored products. Highlights: T. castaneum has a high protein content and is rich in essential amino acids. The most abundant T. castaneum amino acids were valine, lysine and histidine. T. castaneum was rich in minerals and unsaturated fatty acids. T. castaneum had lower saturated versus unsaturated fatty acids, in all life stages.